THE RELATIONS OF STRUCTURATION IN THE BPJS HEALTH PROGRAM AND THE CHANGING OF HEALTH BEHAVIOR - Soemanto, RB; Gutama, TA (Journal of Health Policy and Management, 2020)
Background: The BPJS Health Program supports the improvement of public health.This study aimed to understand the relations of structuration of the BPJS Health Program and changing of health behavior in Surakarta IndonesiaSubjects and Method: A qualitative study was carried out byphenomenological approach.The BPJS participants'program wereprimary informants. The key informants were doctors, nurses, midwives, and other services officers of the community health center (Puskesmas), hospital, andHealth BPJSoffice. The supported informants consisting of the Health Office services, the Population, and Civil Registration Offices, the Communication and Information Services, the Social Services of the Local Government of Surakarta Municipality.Depth interviews and the focus group discussion (FGD) technique were applied to gather data. Data analysis technique using interpretative phenomenology, and theory of structuration from Anthony Giddens for explaining the data.Results: Interactionalpractices in the health service processes produce attitudes, awareness of health services provided.It improves the healthy behavior of the BPJS participants. Rules and regulations of the health center and referenced hospitals accepted and followed by the participant. Doctors and other health care providers work professionally to accommodate patients? needs. The participants reproduce duality structure and roles in the health services delivery processes. The participants as agentsdevelop structuration; whereagents respond to agency of structure of the health services, and vice versa. Patients and health services providershave mutually reinforced roles and benefits. In the course of space and time, the actions of the participants are recurring.Conclusion: Collaboration was developed between the BPJS Office with Puskesmas and hospitals. It brings closer to social relations between patients and health care providers. It was constructed due to understanding and obedience of the participants to the rules, in the forms of procedural rules and doctors? medicalization.Keywords: Relations, Structuration, BPJS Health Program, Health Behavior, ChangeCorrespondence: RB. Soemanto. Department of Sociology, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: Soemanto_rb@yahoo.com, rbsoemanto@gmail.com.Journal of Health Policy and Management (2020), 5(2): 121-126https://doi.org/10.26911/thejhpm.2020.05.02.04